2005
DOI: 10.1002/anie.200462235
|View full text |Cite
|
Sign up to set email alerts
|

The Intermolecular Pauson–Khand Reaction

Abstract: Five membered carbocycles are important building blocks for many biologically active molecules. Moreover, substituted cyclopentenones (e.g. cyclopentenone prostaglandins) exhibit characteristic biological activity. The efficiency and atom economy of the Pauson-Khand reaction render this process potentially one of the most attractive methods for the synthesis of such compounds. Although it was discovered in its intermolecular form, the scope of the intermolecular Pauson-Khand reaction has always been limited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(55 citation statements)
references
References 193 publications
1
53
0
Order By: Relevance
“…(Alkyne)hexacarbonyldicobalt complexes can easily be prepared by treatment of the alkyne with dicobalt octacarbonyl. Such complexes are important in the context of the Pauson–Khand reaction, in which coupling of the alkyne with an alkene results, after CO insertion, in valuable cyclopentenones . Manning et al reported the syntheses of some nonchelate cyclopentadienyl triphenylphosphane alkynyl nickel complexes and performed reactions with dicobaltoctacarbonyl resulting in the formation of trimetallic alkyne hexacarbonyldicobalt complexes with a nickel substituent at the coordinated triple bond , .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Alkyne)hexacarbonyldicobalt complexes can easily be prepared by treatment of the alkyne with dicobalt octacarbonyl. Such complexes are important in the context of the Pauson–Khand reaction, in which coupling of the alkyne with an alkene results, after CO insertion, in valuable cyclopentenones . Manning et al reported the syntheses of some nonchelate cyclopentadienyl triphenylphosphane alkynyl nickel complexes and performed reactions with dicobaltoctacarbonyl resulting in the formation of trimetallic alkyne hexacarbonyldicobalt complexes with a nickel substituent at the coordinated triple bond , .…”
Section: Resultsmentioning
confidence: 99%
“…Such complexes are important in the context of the Pauson-Khand reaction, in which coupling of the alkyne with an alkene results, after CO insertion, in valuable cyclopentenones. [58][59][60][61][62][63][64][65] Manning et al reported the syntheses of some nonchelate cyclopentadienyl triphenylphosphane alkynyl nickel complexes and performed reactions with dicobaltoctacarbonyl resulting in the formation of trimetallic alkyne hexacarbonyldicobalt complexes with a nickel substituent at the coordinated triple bond. [66,67] They mentioned that the parent compound with the unsubstituted alkynyl ligand coordinated to Co 2 (CO) 6 rapidly decomposed, so that only an IR spectrum could be Scheme 5. measured for characterization.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroformylation reactions [200 -216] are used for preparing aliphatic aldehydes whose number of carbon atoms is increased by one, as shown in eqn (32).…”
Section: Hydroformylation Reactionsmentioning
confidence: 99%
“…To date, the vast majority of these applications have been conducted in intra - rather than inter molecular settings. 136 That said, there have been notable examples of the use of intermolecular Pauson-Khand reactions in natural product synthesis. These processes are, as illustrated in the bottom portion of Figure 36, quite complex.…”
Section: Introductionmentioning
confidence: 99%